Role of Level-IV Post-graduation in Basic Sciences in Research Development and Quality Improvement of Graduate Medical Education in Pakistan (Journal of Fatima Jinnah Medical University, 2025)
Medical education has undergone evolutionary and dynamic changes. More emphasis is on curricula to be spirally integrated, learner centered, community oriented and competency-based. The goal remains to provide best evidence-based and patient-centered personalized care. Integration of preclinical and clinical disciplines remains the key to achieve this goal. Thus the role of basic medical science teachers has also evolved to accomplish the required outcome.1 A detailed knowledge of clinically oriented basic medical sciences is a prerequisite to inculcate the lifelong critical thinking and problem-solving skills in healthcare professionals, acquisition of clinical competence, diagnostic accuracy and selection of most appropriate evidence-based management according to patients’ needs.2 To face the dynamic curricular needs, there are growing challenges to the quality of basic medical education in the country. These include lack of motivated and trained basic science faculty, acquisition of teaching skills according to modern day requirements, stepwise clinical integration, barriers in pursuing undergraduate and postgraduate research, limited access to well-maintained data registries and research software in basic sciences.3,4 As per global consensus, competency-based learning in basic medical sciences is essential in present century’s clinical practice and the ability to apply basic medical science concepts to clinical practice is an essential and relevant indicator of educational outcomes in medical institutions.5